2019
DOI: 10.1016/j.abb.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic troponin T mutants with opposing effects on myofilament Ca2+ sensitivity attenuate cardiomyopathy phenotypes in mice

Abstract: Mutations in cardiac troponin T (TnT) associated with hypertrophic cardiomyopathy generally lead to an increase in the Ca2+ sensitivity of contraction and susceptibility to arrhythmias. In contrast, TnT mutations linked to dilated cardiomyopathy decrease the Ca2+ sensitivity of contraction. Here we tested the hypothesis that two TnT disease mutations with opposite effects on myofilament Ca2+ sensitivity can attenuate each other’s phenotype. We crossed transgenic mice expressing the HCM TnT-I79N mutation (I79N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…Moreover, the duration of contractile events is prolonged in MUT iPSC‐CMs. Our findings are in line with recent reports describing molecular disease phenotypes in patient‐specific iPSC‐CMs carrying inherited DCM mutations in sarcomeric proteins [13–15,17,44]. Our comparison of the NNBD‐based strategy with previously established methods for analysis of Ca 2+ handling, force recordings and contractility data in cardiac cells revealed overall comparable results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the duration of contractile events is prolonged in MUT iPSC‐CMs. Our findings are in line with recent reports describing molecular disease phenotypes in patient‐specific iPSC‐CMs carrying inherited DCM mutations in sarcomeric proteins [13–15,17,44]. Our comparison of the NNBD‐based strategy with previously established methods for analysis of Ca 2+ handling, force recordings and contractility data in cardiac cells revealed overall comparable results.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that the TnT‐R141W mutation increases the TnT binding affinity for tropomyosin, thereby resulting in Ca 2+ desensitization of myocyte contraction [15]. Moreover, Ca 2+ desensitization in presence of TnT‐R141W has been elucidated in a double‐transgenic ‘rescue’ mouse model [44]. In line with these reports, we observed a prolonged transient duration and reduced amplitude in Ca 2+ transients from TnT‐R141W (MUT) iPSC‐CMs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In general, myofilament incorporation of troponin variants that cause opposing effects on thin filament Ca 2+ responsiveness are expected to normalize the myofilament Ca 2+ sensitivity Alves et al, 2014Alves et al, , 2017Dieseldorff Jones et al, 2018), and that was what was found in this study. Compared to WT, the 50%:50% mix of D132N/D145E showed similar myofilament Ca 2+ sensitivity and Hill coefficient (n Hill ) values, the latter generally reflecting cooperative processes associated with isometric force generation.…”
Section: Implications For Ctnc Function In the Cardiac Thin Filamentsupporting
confidence: 80%
“…Echocardiography and analysis were performed using a Vevo 2100 high‐resolution in vivo imaging system and workstation as described previously (Dieseldorff Jones et al, 2019; Parvatiyar et al, 2019). Three‐month‐old male and female mice of both genotypes were maintained under light anesthesia with isoflurane (∼2%) during the procedure.…”
Section: Methodsmentioning
confidence: 99%